Curandero : a life in Mexican folk healing - Torres, Eliseo; Sawyer, Timothy L. (Timothy Leighton), 1961- (University of New Mexico Press, 2005)
"Eliseo Torres, known as 'Cheo, ' grew up in the Corpus Christi area of Texas and knew, firsthand, the Mexican folk healing practiced in his home and neighborhood. Later in life, he wanted to know more about the plants and rituals of curanderismo. Torres's story begins with his experiences in the Mexican town of Espinazo, the home of the great curandero El Niño Fidencio (1899-1939), where Torres underwent life-changing spiritual experiences. He introduces us to some of the major figures in the tradition, discusses some of the pitfalls of teaching curanderismo, and concludes with an account of a class he taught in which curanderos from Cuernavaca, Mexico, shared their knowledge with students. Part personal pilgrimage, part compendium of medical knowledge, this moving book reveals curanderismo as both a contemplative and a medical practice that can offer new approaches to ancient problems"--Provided by publisher.